Impacts of human pressure and climate on biodiversity–multifunctionality relationships on the Qinghai–Tibetan Plateau - Ye, Chongchong; Wang, Shuai; Wang, Yi; Zhou, Tiancai; Li, Ruowei (Frontiers in Plant Science, 2023)
Many studies have investigated the effects of environmental context on biodiversity or multifunctionality in alpine regions, but it is uncertain how human pressure and climate may affect their relationships. Here, we combined the comparative map profile method with multivariate datasets to assess the spatial pattern of ecosystem multifunctionality and further identify the effects of human pressure and climate on the spatial distribution of biodiversity-multifunctionality relationships in alpine ecosystems of the Qinghai-Tibet Plateau (QTP). Our results indicate that at least 93% of the areas in the study region show the positive correlation between biodiversity and ecosystem multifunctionality across the QTP. Biodiversity-multifunctionality relationships with increasing human pressure show a decreasing trend in forest, alpine meadow and alpine steppe ecosystems, while an opposite pattern was found in alpine desert steppe ecosystem. More importantly, aridity significantly strengthened the synergistic relationship between biodiversity and ecosystem multifunctionality in forest and alpine meadow ecosystems. Taken together, our results provide insights into the importance of protecting and maintaining biodiversity and ecosystem multifunctionality in response to climate change and human pressure in the alpine region.